PREOPERATIVE RADIOTHERAPY IN ESOPHAGEAL CANCER: A CASE REPORT - Radić, Milica S; Mitić, Dušan; Ćosić, Milica; Simonović, Nataša (Acta medica Medianae, 2021)
Carcinoma of the esophagus is a relatively rare tumor and participates with total morbidity of 1.5%. Every year, around 480000 people in the world are affected, including more men than women, and about 400000 people a year have an death outcome. Most cases are registered in less developed environments, in middle and senior life. The main risk factors include smoking, excessive alcohol consumation, the deficit of certain microelements and vitamins in the diet. The main symptoms are: progredient dysphagia, dyspepsia, while pain, swelling, coughing occur in advanced stages of the disease. The diagnosis is based on a pathohistological confirmation of the disease from the biopsied material taken by the esophagogastroscopy or by the endoscopic resection material. The therapy used in the treatment of esophagus cancers is multidisciplinary. The most common is surgical, radioteraphy, and chemotherapy. Often these three basic forms of therapy are combined. In this case report, the neoadjuvant therapy consisting of chemotherapy according to the PF protocol and transcutaneous radiotherapy gave an extremely good therapeutic response, and the disease from an unresponsive state was converted into a state of radical operability.